The Role of Work Engagement in Mediating Perceived Organizational Support and Organizational Commitment Relationship to Organizational Citizenship Behavior - Tawil, Muhammad Risal; Mattalatta, Mattalatta; Baharuddin, Baharuddin; Umar, Akmal (Ridwan Institute, 2023)
This paper reviews the important role ofwork engagement (WE) in bridging the relationship between perceived organizational support (POS) and organizational commitment (OC) on organizational citizenship behavior (OCB) to private university lecturers. WE is one of the positive behaviors in the form of positive engagement cognitively, emotionally, and physically to increase productivity and morale. High WE is the main capital in creating lecturer OCB.Several previous studies have shown that high POS and OC have not consistently resulted in good OCB.With these considerations in mind, this study presents a WE thatbelieved to be able to strengthen POS and OC relations with OCB. It is hoped that this paper will provide a new perspective on the role of WE and other factors that can improve OCB for lecturers at private tertiary institutions. This study uses a quantitative approach and descriptive design. The research respondents were lecturers spread across 7 tertiary institutions in Baubau City. While data collection was carried out using digital instruments in the form of google forms which were distributed and managed to collect a sample of 257 respondents. The results of this study indicate thatWE has a significant positive influence in bridging the relationship between POS and OC towards OCB.This study suggests paying more attention to WE and OC because they have been proven to significantly contribute to increasing OCB in private university lecturers.